A new mixed integer non-linear programming model for optimal PAT and PRV location in water distribution networks - Morani, Maria Cristina; Carravetta, Armando; D'Ambrosio, Claudia; Fecarotta, Oreste (Urban water journal, 2021)
Water distribution network are energy-demanding systems affected by low efficiency. In such systems, the pressure is generally kept under control by regulation valves to reduce the waste of water due to the leakages. The employment of energy production devices may be an efficient strategy to both reduce waste of water and produce energy, whose feasibility basically depends on the amount of recoverable energy, though. In this study, the optimal location of both pumps as turbines (PATs) and pressure-reducing valves (PRVs) within a literature water distribution network is investigated to maximize the production of energy and water savings. A new mixed integer non-linear model has been developed and a global optimization solver has been employed to perform the optimization. According to the results, the new optimization ensures good solutions, in term of water and energy savings, when compared with other procedures in literature.